Constructing a Hetero-interface Composed of Oxygen Vacancy-Enriched Co3O4 and Crystalline–Amorphous NiFe-LDH for Oxygen Evolution Reaction - Lv, Junjun; Wang, Linmeng; Li, Rushuo; Zhang, Kaiyue; Zhao, Danfeng; Li, Yaqiong; Li, Xiangjun; Huang, Xiubing; Wang, Ge (ACS catalysis, 2021)
The development of high-performance electrocatalysts is a highly efficient strategy to optimize the sluggish kinetic property of the oxygen evolution reaction (OER). Herein, we synthesize a kind of nickel foam (NF)-supported electrocatalyst composed of a one-dimensional Co3O4 nanowire as the core and a two-dimensional NiFe-LDH nanosheet as the shell (denoted as NiFe-60/Co3O4@NF). Fluorine is introduced into the precursor Co(OH)F of Co3O4, which results in improved thermal stability and significantly increased regularly distributed oxygen vacancies, while the electrochemically deposited NiFe-LDH nanosheets possess a crystalline/amorphous hybrid structure. As a result, the hetero-interface mainly constituting Ni species from NiFe-LDH and Co3O4 from Co(OH)F contributes to the interaction between Co and Fe species and facilitates the electron transfer. Simultaneously, the interaction between oxygen vacancies in Co3O4 and coordinatively unsaturated Fe species in the amorphous area in NiFe-LDH is also determined, finally completing the electron backtracking. Benefiting from these factors, only low overpotentials of 221 and 257 mV are required to deliver the current densities of 100 and 500 mA cm–2, respectively, with a quite small Tafel slope of 34.6 mV dec–1 during OER for the well-designed NiFe-60/Co3O4@NF electrocatalyst.